The mediating role of innovation capability on ICT support, entrepreneurial orientation support and SMES' performances: a conceptual approach - Yap, Luen Her; Ahmad, Shuhymee; Hoe, Chee Hee (2019)
This study is intended to investigate the impact of internal support, such as Information and communication technology (ICT) support, and entrepreneurial orientation support (EOS) that affects small and medium enterprises’ (SMEs) performances in Malaysia which are mediated by the innovation capability. This paper has revealed the literature review of the determinant dimensions, which include ICT support and entrepreneurial orientation support towards innovation capability as a mediating role, which influence SMEs’ performances. The contribution of this paperis in merging those constructs into a comprehensive conceptual framework model to enable a better understanding and clarity about how the efforts should be made to boost SMEs’ growth and development. Next, the hypotheses will be developed from the proposed conceptual framework model. Lastly, implications and suggestions for future studies will be presented.